POTENTIAL INFLUENCE OF URBAN SPRAWL AND CHANGING LAND SURFACE TEMPERATURE ON OUTDOOR THERMAL COMFORT IN LAGOS STATE, NIGERIA - Obiefuna, Jerry N.; Okolie, Chukwuma J.; Nwilo, Peter C.; Daramola, Olagoke E.; Isiofia, Lawrence C. (Quaestiones Geographicae, 2021)
The continuous monitoring of the relationship between land surface temperature (LST) and land cover change is imperative for an inquiry into the potential impact of LST on human well-being, including urban outdoor thermal comfort in Lagos State, Nigeria. Using Landsat imagery, this study assessed land cover and LST changes from 1984 to 2019. Land cover was extracted, LST was determined from Landsat imageries and the land cover changes were linked to LST using the contribution index (CI). Afterwards, the universal thermal climate index (UTCI) was calculated to determine the heat stress levels. Findings confirm the presence of urban sprawl and new growth areas in previously rural Local Government Areas (LGAs) eastward, northward and westward of Lagos metropolis and in regions which lie on the fringe of the state’s border with Ogun State. Also, a very strong link between high LST intensities and increasing concentration of urban areas in rapidly growing LGAs has been observed. This link further confirms the increased warming of the state, with an increase in mean LST of 2.16°C during 1984–2019. The UTCI which was used to gauge the influence of LST on outdoor thermal comfort ranged from moderate to strong heat stress levels. This study helps to strengthen the case for definite policies and actions which should be aimed at achieving moderate urban development through increased urban tree canopy/green infrastructure provision and carbon sequestration activities in urban design/landscape design, in Lagos State.